Espaços não formais de ensino como estratégia para práticas de educação ambiental nas escolas públicas de Guaçuí/ES - Correa, Mariana Spala (2019)
The educational process can take place in both formal and non-formal teaching spaces. The acquisition of new knowledge, especially in an environmental aspect, should not be limited to formal teaching spaces only. There are other spaces that, together with the school, contribute to an education with new horizons and perspectives, contributing to a critical and reflective discussion of Environmental Education, as well as the construction of values and responsible attitudes towards the environment and the socioeconomic development with the environment. sustainable. Considering Environmental Education as a cross-cutting theme that should be present at all levels of education and knowledge areas, the question arose as to how non formal teaching spaces are explored for Environmental Education by teachers of public schools in the municipality of Guaçuí/ES. The aim of this research was to investigate the relationship of Environmental Education with non-formal teaching spaces from the perspective of these teachers. We realize the need to build a citizenship education and expand teaching spaces, through continuous and permanent reflective and critical learning, from the use of non-formal teaching spaces in Environmental Education practices and actions, based on the ideas of Paulo Freire. We conducted a qualitative research, based on the application of a questionnaire and interview, aiming to obtain information regarding the understanding, approach and perspective of these teachers in relation to Environmental Education and non-formal teaching spaces. The results point to a conservationist view of teachers in relation to Environmental Education, which reflects the use of the textbook as the main pedagogical resource and the classroom as the main place to approach this theme. The understanding of non-formal teaching spaces as environments outside the school whose purpose is related to practical activities and as main difficulties in the development of activities on environmental themes in non-formal teaching spaces, lack of transportation, financial resources and extensive curriculum.